The effect of active myokinetic chain release and stretching on physical performance amongst young racquet sports players - Das, Ashirbad; Saini, Preeti; Rizvi, Moattar Raza; Sethi, Priyanka; Sharma, Ankita; Ahmad, Irshad (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Muscle imbalance is frequently observed according to research findings. Muscles that have been shortened for a lengthy period become tight. Modalities, posture changes, and releases can all be used to treat this condition. Muscle soreness is a myogenic condition that results from deep releases. A joint’s range of motion is reduced and pain is experienced as a result of adhesions and inflammation caused by the rupture of taut bands because of excessive pressure. Aim of Study. The aim was to examine the effects of active myokinetic chain release therapy (AMRT) and stretching on physical performance amongst adolescent racquet sport players with misalignment of fascial tissue. Material and Methods. Eighty racquet sports players having muscle imbalance as tested by the Bunkie test were randomly divided into two groups receiving AMRT and stretching, respectively. They were tested for different biomotor abilities, targeting lower back and hamstring flexibility, agility as well as endurance, with functional ability, speed of the racquet, pulse rate, and oxygen saturation used to assess physical performance. Results. AMRT resulted in better results in improving the biomotor abilities as compared to stretching in different biomotor abilities, but there was a significant change from pre- to post-assessment. Conclusions. While AMRT can increase biomotor and physical performance in elite athletes, there is no key procedure to apply this intervention to any player, yet this appears to be a very easy and adequate protocol for the athletic population to generate the immediate effect.
Keywords: stretching; Bunkie test; racquet players; active; myokinetic chain release therapy; biomotor abilities